Soils of the Tasersiaq Area, Greenland. - Holowaychuk, N.; Everett, K. R, (Meddelelser om Grønland, 1972)
Ten soil series are recognized for the ice-free area of Tasersiaq, Greenland. A profile description and pertinent chemical and physical data are presented for each series. For the most part the soils have developed in sandy till and kame terrace deposits under drainage conditions ranging from standing water to those which can be termed excessively well drained. It is believed that the soils of the Tasersiaq area represent only a few thousand years of development under a climate similar lo lhe present. The combination of factors of rapid internal drainage, relative site stability and heath vege tation, have under present climatic conditions allowed the zonal process of podzolization to be weakly expressed. Where internal drainage is partly or completely restricted, and sile instability occurs, a series of half-bog and tundra soils have developed.